Demotivation and Self-Efficacy: Exploring Causes, Effects, and Solutions Through Bandura’s Theory - Lionel Jacob Haseya Sihaloho; Edward Aaron (Education : Jurnal Sosial Humaniora dan Pendidikan, 2026)
Demotivation is a recurring problem in education, work, and personal development because it weakens effort, persistence, and confidence in goal pursuit. This article examines demotivation through Albert Bandura’s self-efficacy theory in order to clarify its causes, effects, and possible solutions. Using a qualitative conceptual design based on literature review and Socratic analysis, the study synthesizes established scholarship on self-efficacy, motivation, anxiety, social persuasion, and academic performance. The analysis shows that demotivation often emerges when valued tasks are reinterpreted as threatening, particularly under conditions of stress, fear of judgment, fatigue, and low confidence. In such situations, self-efficacy becomes a crucial mediating belief that shapes whether individuals persist, withdraw, or recover. The discussion identifies four major pathways for restoring motivation: mastery experiences, constructive vicarious experience, supportive social persuasion, and regulation of emotional and physiological states. At the same time, the article argues that Bandura’s framework, while highly influential and practically useful, has limitations when demotivation is shaped by structural constraints, repeated social failure, or forms of inner meaning not fully captured by efficacy beliefs alone. The article contributes a focused conceptual synthesis that positions demotivation as a confidence-related disruption in goal-directed action and offers practical implications for students, educators, and professionals seeking to rebuild motivation in demanding contexts.